2013
DOI: 10.1007/s00404-013-2929-2
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy: a review

Abstract: It was concluded that review data reflect a decrease in surgical treatment and not an actual decline in EP occurrence so that further new avenues are needed to explore early detection of the EP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
1
17

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 120 publications
2
93
1
17
Order By: Relevance
“…In this scenario, the extravillous CTB subpopulation penetrates the uterine wall and spiral arteries to the degree that is required to sustain pregnancy for varying periods of time, but short of the duration of normal pregnancy. This may be a result of the highly invasive nature of these placental cells (37), which enables them to anchor not only to the uterus, but also to ectopic sites that they penetrate in search of a blood supply (38). Thus, we concluded that failed decidualization restricts the depth of CTB invasion such that pregnancy is maintained but ends in sPE.…”
Section: Discussionmentioning
confidence: 85%
“…In this scenario, the extravillous CTB subpopulation penetrates the uterine wall and spiral arteries to the degree that is required to sustain pregnancy for varying periods of time, but short of the duration of normal pregnancy. This may be a result of the highly invasive nature of these placental cells (37), which enables them to anchor not only to the uterus, but also to ectopic sites that they penetrate in search of a blood supply (38). Thus, we concluded that failed decidualization restricts the depth of CTB invasion such that pregnancy is maintained but ends in sPE.…”
Section: Discussionmentioning
confidence: 85%
“…It refers to the pregnancy occurring outside the uterine cavity that constitutes 1.2-1.4 % of reported pregnancies [6].…”
Section: Resultsmentioning
confidence: 99%
“…The EP presents a major health problem for women of child-bearing age, constituting 1.2-1.4% of all reported pregnancies. Most specified risk factors are of maternal origin: pelvic inflammatory disease, Chlamydia trachomatis infection, smoking, tubal surgery, induced conception cycle as well as endometriosis [8]. During the past 40 years, its incidence has been steadily increasing concomitant with increased sexually transmitted disease (STD) rates and associated salpingitis (inflammation of the Fallopian tubes).…”
Section: Introductionmentioning
confidence: 99%